Para além do riso: charges, consciência histórica e Ensino de História - SILVA, Neles Maia da (Universidade Federal do Pará, 2023)
This work aims to discuss the reading and production of cartoons by primary school students, focusing on the debates around historical consciousness. The problem becomes pertinent, since the images are almost always used as illustration or reinforcement and not as historical sources. In this sense, we seek to understand how students read and analyze images, especially the cartoon and what relations exist between their productions and historical consciousness. We used the workshop-class methodology of Isabel Barca and the theoretical debates of Jörn Rüsen, André Chervel, Juliá Dominique in dialogue with the national historiography of Maria Auxiliadora Schmidt, Circe Bittencourt among others. The sources of our research were various cartoons, school documents, student cartoons, socioeconomic records and texts produced by them. The research was developed at the Guajarina Menezes School in São João de Pirabas-PA, with a 9th grade class from Elementary School. The product of this research was a set of cartoons produced by the students and teacher on different subjects. It was considered at the end of the research that the historical consciousness is not only present in the students, but also presents itself in different ways, in view of their world readings, their thematic choices in producing the cartoons and their experiences. Students were not mere receivers of knowledge, but they also constructed and were subject in this process.